Ethnic differences in clinical outcome of patients presenting to the emergency department with chest pain - de Hoog, Vince C; Lim, Swee Han; Bank, Ingrid EM; Gijsberts, Crystel M; Ibrahim, Irwani B; Kuan, Win Sen; Ooi, Shirley BS; Chua, Terrance; den Ruijter, Hester M; Pasterkamp, Gerard; Tai, E Shyong; Gao, Fei; et al. (European heart journal. Acute cardiovascular care, 2016)
Background: Ethnicity, although known to influence cardiovascular outcome in assorted clinical settings, has not been investigated previously as a risk factor in patients presenting to the emergency department with suspected acute myocardial infarction. Methods: In this multi-ethnic cohort study conducted in Singapore and The Netherlands, 2784 patients presenting to the emergency department with chest pain were enrolled (788 Caucasians, 1281 Chinese, 404 Indians and 311 Malays) and were followed up for 1 year. Results: Although Caucasian patients on average were older and had incurred more cardiovascular adverse events, the Asian ethnic groups carried a greater burden of cardiovascular risk factors. Caucasian and Malay patients were most frequently diagnosed with acute myocardial infarction (Caucasians 11.2%, Chinese and Indians 6.4%, Malays 10.6%, P<0.001), also after correction for baseline differences. Chinese and Indian patients, however, more often had unstable angina. Asian patients had strikingly more extensive coronary artery disease than Caucasian patients (triple-vessel disease: Caucasians 6.5%, Chinese 22.8%, Indians 32.4%, Malays 32.8%, P<0.001) and Chinese patients with myocardial infarction more frequently underwent coronary revascularisation compared with Caucasian patients (Caucasians 41.4%, Chinese 67.5%, Indians 62.5%, Malay 46.7%, P=0.005). Ethnicity was not an independent predictor of major adverse cardiovascular events during 1-year follow-up in all chest pain patients. Conclusions: The prevalence of myocardial infarction and unstable angina, revascularisation rate and extent of coronary artery disease differ significantly among chest pain patients of different ethnic groups. These findings have important clinical implications and support consideration of ethnicity in risk stratification and determination of the patient management strategy in patients with symptoms suggestive of myocardial infarction.